Current Drugs with Potential for Treatment of COVID-19: A Literature Review - Md Insiat Islam Rabby (Frontiers Media S.A., 2020)
Purpose: SARS-CoV-2 first emerged in China in December 2019 and rapidly spread worldwide. No vaccine or approved drug is available to eradicate the virus, however, some drugs that are indicated for other afflictions seems to be potentially beneficial to treat the infection albeit without unequivocal evidence.   The aim of this article is to review the published background on the effectiveness of these drugs against COVID-19 Methods: A thorough literature search was conducted on recently published studies which have published between January 1 to March 25, 2020. PubMed, Google Scholar and Science Direct databases were searched Results: A total 22 articles were found eligible. 8 discuss about treatment outcomes from their applied drugs during treatment of COVID-19 patients, 4 report laboratory tests, one report animal trial and other 9 articles discuss recommendations and suggestions based on the treatment process and clinical outcomes of other diseases such as malaria, ebola, severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS). The data and/or recommendations are categorized in 4 classes: (a) anti-viral and anti-inflammatory drugs, (b) anti-malaria drugs, (c) traditional Chinese drugs and (d) other treatments/drugs. Conclusion: All examined treatments, although potentiality effective against COVID-19, need either appropriate drug development or clinical trial to be suitable for clinical use.